2010
DOI: 10.1590/s0004-28032010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese validation of the Rome III diagnostic questionnaire for functional dyspepsia

Abstract: The Rome III Diagnostic Questionnaire for Functional Dyspepsia is ready to be used in clinical researches in lusophone countries, as it has been successfully validated in Portuguese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
2
15
0
3
Order By: Relevance
“…15 A translation of the Rome III questionnaire into Portuguese discriminated medically diagnosed patients with FD from health controls with a sensitivity of 91% and specificity of 95%. 16 It has been reported that a sensitivity of the modified Rome III Diagnostic Questionnaire differs among the Asian countries, 17 suggesting that socio-cultural perspective and/or the linguistic nuances might be taken into account to translate the original questionnaire into different languages.…”
Section: Discussionmentioning
confidence: 99%
“…15 A translation of the Rome III questionnaire into Portuguese discriminated medically diagnosed patients with FD from health controls with a sensitivity of 91% and specificity of 95%. 16 It has been reported that a sensitivity of the modified Rome III Diagnostic Questionnaire differs among the Asian countries, 17 suggesting that socio-cultural perspective and/or the linguistic nuances might be taken into account to translate the original questionnaire into different languages.…”
Section: Discussionmentioning
confidence: 99%
“…The Rome III questionnaire is a standardized and trustworthy instrument with a validated version for Brazilian Portuguese (40) .…”
Section: Methodsmentioning
confidence: 99%
“…For dyspepsia diagnosis, the proposed scheme drawn up by experts and determined by the consensus (43) , considering the Rome III questionnaire items (40) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal symptoms were analyzed in patients and controls using a standardized questionnaire that was previously validated (17). The following esophageal symptoms were analyzed: dysphagia, heartburn and regurgitation.…”
Section: Gastrointestinal Symptomsmentioning
confidence: 99%